Elastomeric compositions and articles comprising same

By using a composition of high content of hydrothermal treatment of lignin (HTC lignin) and elastomeric polymers in rubber products, the problem of insufficient gas permeability when lignin replaces carbon black in the prior art is solved, and lower gas permeability and improved mechanical properties are achieved.

CN119585365APending Publication Date: 2025-03-07UPM KYMMENE OYJ
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280098294.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has not been able to effectively reduce gas permeability when recyclable materials such as lignin are used to replace carbon black to produce sustainable rubber products, resulting in poor performance of the products in gas barrier applications.

Method used

Using compositions containing elastomeric polymer and hydrothermal treated HTC lignin, the HTC lignin is present in an amount of 50 phr or more, preferably having a particle size D90 of 5 μm or more and a surface area of ​​40 m2/g or less.

Benefits of technology

The gas permeability, tensile properties and compressive deformation properties of the elastomer containing the composition are significantly improved, especially in the high temperatures, showing improved mechanical properties and reduced density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005246206200000101
    Figure BDA0005246206200000101
Patent Text Reader

Abstract

The present invention relates to a composition comprising an elastomeric polymer and 50 phr (parts per 100 parts of polymer) or more of HTC lignin, wherein the HTC lignin has a particle size D90 of 5 [mu] m or more as determined by ISO 13320: 2020 and an STSA surface area of 40 m2 / g or less as determined by ASTM D 6556-14. The invention also provides an article comprising the composition and the use of the composition in a gas barrier.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a composition comprising an elastomeric polymer and hydrothermally treated lignin, an article comprising the composition and the use of the composition in a gas barrier. Background Art

[0002] Carbon black is widely used as a filler for rubber products such as tires. However, carbon black is usually produced from fossil materials and is therefore not a sustainable material. In order to produce rubber products on a more sustainable and environmentally friendly basis, many attempts have been made to replace carbon black with renewable materials such as lignin. However, these attempts have not yet produced satisfactory rubber compositions, and the corresponding products have not yet been commercialized on a large scale.

[0003] WO 2016 / 185351 discloses compounds for tire sealants comprising kraft lignin. Other uses of lignin in rubber blends are disclosed in WO 2020 / 140155 and Aini et al., Front. Mater. 6 (2020) 329.

[0004] EP-3 243 877 discloses a pneumatic tire comprising hydrothermally carbonized lignin. Hydrothermally treated lignin (also referred to as HTC lignin) is derived from lignin that has been thermochemically converted in the presence of water (see, for example, Correa et al., Materials 11 (2018) 1568). The HTC lignin of EP-3 243 877 has a carbonization temperature of less than 150 m / s. 2 / g surface area. It is said that HTC lignin can be used in an amount of 75% by weight of the total rubber composition. For non-tread samples containing 46phr (parts / 100 parts of rubber), EP-3 243 877 proposes that the tan δ of the rubber composition containing HTC lignin is lower than the tan δ of the rubber composition containing carbon black. Other advantages in tensile strength are claimed. The permeability of air and gas is not mentioned.

[0005] WO2020 / 202125 discloses a liner comprising HTC lignin as a partial substitute for carbon black. WO2020 / 202125 proposes the use of 15-45 phr of HTC lignin, which preferably has a carbon black content of 30-55 m 2 / g surface area, 1-4μm D 50 and D of 5-8 μm 90 Rubber mixtures containing carbon black and 30 phr of HTC lignin are said to show improved oxygen barrier properties compared to carbon black and a combination of carbon black and kraft lignin (see above-mentioned WO 2016 / 185351), without changing M300%.

[0006] EP-A 3 974 470 discloses a composition comprising a halogenated butyl rubber and 50 to 90 phr of a polyol having a content of 10 to 50 m 2 The use of these fillers reduced the gas permeability by 15% or less compared to carbon black. Summary of the invention

[0007] The present invention provides compositions with reduced gas permeability and other beneficial properties. The compositions according to the present invention are particularly beneficial when used in gas barriers or in articles requiring gas barrier properties such as hoses, films, hollow articles and tires. The compositions are particularly useful or used as inner liners for pneumatic tires.

[0008] The composition according to the present invention comprises an elastomeric polymer and HTC lignin. The HTC lignin is present in an amount of 50 phr (parts per 100 parts of polymer) or more. Preferably, the HTC lignin has a particle size D of 5 μm or more as measured by ISO 13320. 90 and 40 m as determined by ASTM D 6556-14 2 / g or less surface area.

[0009] Surprisingly, it was found that the composition according to the invention makes it possible to significantly improve several properties of elastomers containing the composition, including the gas permeability. DETAILED DESCRIPTION

[0010] The polymers of the present invention are elastomers including rubbers and polymer-rubber blends and composites.

[0011] The composition of the present invention may include various types of elastomers, such as styrene-butadiene polymers and block copolymers, polyisoprene, natural rubber, polybutadiene, ethylene propylene rubber, silicone elastomers, fluoroelastomers, polyurethane elastomers and nitrile rubber. Styrene butadiene (SBR) and butadiene (BR) are the most common rubber polymers in the tire industry. The composition of the present invention may include one or more elastomers.

[0012] The elastomer of the present invention can be any elastomer including natural rubber and synthetic rubber. The rubber used herein is a diene polymer or a diene-containing copolymer derived from butadiene, isobutylene and isoprene. Particularly preferred are isobutylene and isoprene copolymers (also known as butyl rubber) and corresponding halogenated rubbers (also known as halogenated butyl rubber).

[0013] Butyl rubber is a synthetic copolymer of isobutylene (usually 98-99 wt%) and isoprene (usually 1-2 wt%). It is characterized by a very low unsaturation content and has unique chemical and physical properties. Butyl rubber exhibits low gas permeability and high chemical resistance.

[0014] Butyl rubber is typically produced by cationic copolymerization of isobutylene and isoprene in the presence of a Friedel-Crafts catalyst at low temperatures, such as about -100° C. or -90° C. Halogenated butyl rubber can subsequently be produced, for example, by reacting a hexane solution of butyl rubber with elemental bromine or chlorine.

[0015] Halogenated butyl rubber can be obtained by halogenating butyl rubber during or after polymerization. Chlorinated and brominated butyl rubbers show improved compatibility with other polymers and higher cure rates than butyl rubber. Allyl C-Br or C-CI bonds promote vulcanization and allow fundamentally different cure chemistry from other elastomers that rely on the reactivity of allyl C-H bonds. Halogenated butyl rubber can, for example, only be cured by ZnO in the absence of sulfur, thereby producing vulcanized rubber. This unique cure chemistry can, for example, promote co-vulcanization with other rubbers such as natural rubber (NR) and styrene-butadiene rubber.

[0016] Halogenated butyl rubber used in the formulation of the present invention may include a copolymer of isobutylene (e.g., 95-99.5 wt %, or preferably 98-99 wt %) and isoprene (e.g., 0.5-5 wt %, 0.3-6 wt %, or 1-2 wt %, based on the total weight of the monomers). Chlorinated butyl rubber may, for example, contain chlorine in an amount of about 0.1 to about 6 wt %, or about 0.8 to about 15 wt % (based on the weight of the polymer). Brominated butyl rubber may, for example, contain bromine in an amount of about 0.1 to about 15 wt %, or about 1 to about 6 wt % (based on the weight of the polymer). In halogenated butyl rubber, the halogen content is limited to the isoprene content and is also limited to the fact that only a portion of the double bonds are halogenated. In typical halogenated butyl rubbers, 60% of the double bonds may have allyl halogen substituents.

[0017] In a preferred embodiment, the rubber mixture comprises a halogenated butyl rubber, which may contain at least one other diene rubber. In a particularly preferred embodiment, the rubber mixture comprises 31 to 100 phr of at least one halogenated butyl rubber and 0 to 69 phr of at least one other diene rubber. In the case of innerliners, polymers derived from isobutylene and p-bromomethylstyrene are preferred. In such polymers, high bromomethyl-styrene concentrations (e.g. 40 to 60 mol %, especially 50 mol %) are particularly preferred. Such commercially available polymers are Exxpro from Exxon Mobile TM 3563.

[0018] The other diene rubber may be selected from the group consisting of natural rubber, butyl rubber, polybutadiene rubber, styrene-butadiene copolymer, synthetic polyisoprene, natural polyisoprene, styrene-isoprene copolymer, styrene-isoprene-butadiene terpolymer, solution polymerized styrene-butadiene rubber, and emulsion polymerized styrene-butadiene rubber, and / or ethylene propylene diene rubber.

[0019] The rubber component may be functionalized using hydroxyl and / or epoxy and / or siloxane and / or amino and / or phthalocyanine and / or aminosiloxane and / or carboxyl and / or other functionalization systems that can chemically bond to the light-colored filler used.

[0020] Fillers are used to improve the mechanical properties of elastomers and vulcanized or cross-linked elastomers and rubbers. Typical examples are carbon black and silica. In tire manufacturing and the rubber industry, carbon black and silica are widely used as fillers. About 93% of carbon black is used in rubber compounding, and it is generally divided into two major categories: mechanical rubber products (i.e. hoses and automotive belts) and tires.

[0021] The filler of the present invention comprises hydrothermal carbonized lignin, also known as HTC lignin. Lignin is the second most abundant natural resource. It is an aromatic polymer that keeps cellulose and hemicellulose together in plants, strengthens the cell wall and protects plants from parasites and diseases. The complex structure of amorphous lignin is formed by the connection of different functional groups such as methoxyl, phenol, hydroxyl and carbonyl. Huge amounts of lignin by-products are produced by the paper and pulp industry, and about 98% of them are usually burned to generate energy or simply abandoned in landfills.

[0022] Hydrothermal carbonization is a thermochemical process of treating biomass under pressure and in the presence of hot water and / or steam. In contrast to pyrolysis, biomass is not completely decomposed during HTC, and the products are solid carbon-rich material, a gas phase consisting mainly of CO2, water and water-soluble compounds.

[0023] HTC lignin can be prepared from any kind of lignin-containing starting material, such as lignin-containing waste materials and lignin in solid or dissolved form and mixtures thereof. A high lignin content of 60 wt % or more, preferably 80 wt % or more, or still better more than 90 wt % in the starting material is preferred.

[0024] Preferred lignin-containing raw materials are black liquor from woody biomass digestion or solids prepared therefrom, solids from enzymatic hydrolysis of woody biomass, black liquor from woody biomass digested with sulfites (lignin sulfonates), or solids or liquids prepared by digesting woody biomass with solvents (e.g., organosolv lignin). In a preferred embodiment of the invention, the lignin is from a side stream in the enzymatic hydrolysis of a lignocellulosic raw material. This preferred starting material is also referred to as EH lignin.

[0025] Lignin-containing biomass can be selected from the group consisting of: kraft lignin, steam explosion lignin, biorefining lignin, supercritical separation lignin, hydrolysis lignin, flash precipitation lignin, biomass-derived lignin, lignin from alkaline pulping, lignin from soda process, lignin from organic solvent pulping, lignin from alkaline process, lignin from enzymatic hydrolysis, and any combination thereof. In one embodiment, lignin is wood-based lignin. Lignin can be derived from softwood, hardwood, annual plant or any combination thereof.

[0026] "Kraft lignin" is lignin derived from kraft black liquor. Black liquor is an alkaline aqueous solution of lignin residues, hemicellulose, and inorganic chemicals used in the kraft pulping process. Black liquor from the pulping process contains components derived from different softwood and hardwood species in varying proportions. Kraft lignin can be separated from black liquor by different techniques including, for example, precipitation and filtration.

[0027] The term "flash precipitated lignin" is to be understood as lignin which has been precipitated from black liquor in a continuous process by lowering the pH of the black liquor stream to a precipitation level for lignin using a carbon dioxide-based acidulant, preferably carbon dioxide, under the effect of an overpressure of 200-1000 kPa and by suddenly releasing the pressure to achieve lignin precipitation. Flash precipitated lignin particles having a particle size of less than 2 μm form agglomerates which can be separated from the black liquor using, for example, filtration.

[0028] Lignin can be derived from the organosolv process, which is a pulping technique that uses organic solvents to dissolve lignin and hemicellulose.

[0029] Lignin can be slurried or dissolved to achieve hydrothermal conversion. Preferably, lignin is dissolved in an alkaline solution such as NaOH. Dissolution can be achieved by heating a mixture of lignin and alkaline solution to about 80°C, adjusting the pH to a value greater than 7, such as 9-11, and mixing the mixture of lignin and alkaline solution for a predetermined time. The mixing time can last for about 2-3 hours. The exact pH value is determined based on the grade target of the product.

[0030] The slurry can be directly subjected to hydrothermal treatment or fed to a separation unit, where the precipitated lignin can be separated from the slurry.

[0031] Hydrothermal carbonization can be carried out in a reactor (HTC reactor) or in several parallel reactors operated in batch mode if necessary. The dissolved lignin can be preheated and then enter one or more HTC reactors. The temperature in one or more HTC reactors can be 150-250°C, and the pressure can be 20-30bar. The residence time in one or more HTC reactors can be about three to six hours. In the HTC reactor, lignin is carbonized, and stable lignin derivatives with high specific surface area can be precipitated. The slurry containing carbonized lignin formed can be removed and cooled subsequently.

[0032] The lignin-containing starting material (preferably in the form of a lignin solution) is subjected to a hydrothermal carbonization (HTC) process. For example, HTC lignin can be obtained by heating the lignin-containing starting material to a temperature of 150 to 350° C., preferably 150 to 250° C., in the presence of water at an autogenous pressure of typically 10 to 40 bar. The heat treatment can be maintained for 30 minutes and up to 8 hours or longer. Preferably, the treatment is completed within 1 to 6 hours or more preferably within 2 to 4 hours.

[0033] For the hydrothermal carbonization of lignin-containing raw materials, preferably at least a portion of the lignin is dissolved. This partial or complete dissolution can be achieved by adjusting the pH to >7, preferably >9 and most preferably >10. A pH of 10 to 12, preferably 10 to 11 before HTC treatment advantageously affects the particle size distribution according to the use of the present invention. In a preferred embodiment, the lignin used for the hydrothermal treatment is in solution.

[0034] Dissolution may also be assisted by raising the temperature to above 50° C., for example 70 to 90° C. and preferably 80° C. Dissolution conditions should be maintained for at least 5 minutes, more preferably at least 10 minutes, more preferably at least 15 minutes, particularly preferably at least 30 minutes, specifically at least 45 minutes but less than 300 minutes.

[0035] For the present invention, it is not necessary for all the lignin to be dissolved in the liquid. However, advantageously, more than 50%, particularly preferably more than 60%, further preferably more than 70%, particularly preferably more than 80%, in particular more than 90% of the lignin is dissolved in the liquid.

[0036] In a particularly preferred embodiment, the mixture of at least partially dissolved lignin also comprises at least one cross-linking agent capable of reacting with the functional groups of lignin. Such cross-linking compounds may have aldehydes, carboxylic acids, epoxy, hydroxyl, isocyanate or other functional groups. The functional groups of the cross-linking agent should be capable of reacting twice with the functional groups of lignin. If the functional group can only react once, the cross-linking agent should contain at least two such groups. Aldehydes and especially formaldehyde are preferred. The cross-linking agent may be added in the dissolving step and / or the HTC step. The reaction of the cross-linking agent with the lignin may also be an intermediate step between the dissolving and HTC steps, and may require pH adjustment to react.

[0037] The crosslinking agent should be used in excess relative to the crosslinkable groups of lignin. This excess can be 1.5, 2 or even 4 times. An amount exceeding 4 times the excess is unnecessary and therefore economically unrecommended. A typical amount is less than 40 wt %, less than 35 wt % or preferably less than 25 wt % based on the weight of lignin. Specifically, in the case of formaldehyde, the amount can be lower than less than 10 wt % or even less than 5 wt %.

[0038] The amount and type of cross-linking agent helps to adjust the surface area of ​​the product obtained in the HTC step. The use of a cross-linking agent increases the surface area of ​​the HTC lignin, whereby generally the surface area also increases with increasing amount of cross-linking agent.

[0039] The HTC lignin used in the present invention has a particle size D of 5 μm or more as measured by laser diffraction according to ISO 13320:2020. 90 . Particle size of HTC lignin D 90 Preferably, it is 8 μm or more, such as 10 μm or more. Particularly preferred is a D of 20 μm or more or even 30 μm or more. 90 value.

[0040] In the measurement according to ISO 13320:20, the HTC lignin is suspended in distilled water and the particle size distribution is measured by laser diffraction. Before and / or during the measurement of the particle size distribution, the sample to be measured is dispersed by ultrasound until a stable particle size distribution is obtained in several measurements.

[0041] The particle size distribution can be affected by certain process parameters. For example, particle size control can be achieved by adjusting the dry matter content of the feed, the pH of the feed, the inorganic ion concentration of the feed, and the temperature and residence time during the hydrothermal treatment. Advantageously, the dry matter concentration of the feed does not exceed 40% by weight (based on the feed), preferably not more than 20% by weight and most preferably not less than 10% by weight. The pH is advantageously 7 or higher, such as 8.5 or greater or even 11 or higher. The inorganic ion value measured by conductivity is 10mS / cm to 200mS / cm, preferably 10mS / cm to 150mS / cm, more preferably 10mS / cm to 50mS / cm, further preferably 10mS / cm to 40mS / cm, specifically preferably 10mS / cm to 25mS / cm (determined by the conductivity of the measuring probe of PCE-PHD1 at 20°C to 25°C). The temperature of the hydrothermal treatment may be limited to a maximum of 200° C. to 250° C., preferably a maximum of 210° C. to 245° C. Residence times of 1 minute to 6 hours, such as 30 minutes to 4 hours or 1 to 3 hours, are also useful. The above measures may also be used in combination.

[0042] If desired, the particle size can also be adjusted by separation or by mixing different HTC lignin materials. In liquid or gaseous media, gravity separation is a suitable method. The equipment used for separation is well known to those skilled in the art. Examples include cyclone separators, especially hydrocyclones in the case of liquids, centrifuges or classifiers (air classifiers). However, the present invention is not limited to the use of specific equipment. All equipment that allows separation can be used, such as fluidized bed equipment, sieves, etc. Different types of separations can also be combined.

[0043] The obtained HTC lignin has a 40m 2 / g or less, more preferably 30m 2 / g or less, such as 25, 20, 15 or 10m 2 / g or less STSA. STSA surface area is determined according to ASTM D 6556-14. STSA (Statistical Thickness Surface Area) is an indication of the outer surface of the HTC lignin particles.

[0044] Advantageously, the BET specific surface area of ​​the HTC lignin of the invention deviates only by a maximum of 20%, preferably by a maximum of 15%, more preferably by a maximum of 10% from the STSA surface. According to Brunauer, Emmett and Teller, the BET surface area is determined as the total surface area of ​​the outer and inner surfaces by nitrogen adsorption of the particles. The method for determining the BET surface is also disclosed in ASTM D6556-14.

[0045] Compositions according to the present invention may also include curing activators or dispersants, such as stearic acid (as an example), and other processing aids, such as naphthenic oils. Processing aids, emulsifiers or dispersants may be, for example, ammonium or alkali metal salts of C12 to C24 fatty acids, such as ammonium, sodium or potassium salts of oleic acid, palmitic acid, stearic acid or linoleic acid. Alternative dispersants include ammonium and alkali metal salts of polyethoxylated sulfates of C6 to C20 alkyl alcohols or polyethoxylated alkylphenoxyethanol and acid esters (phthalic acid, adipic acid, phosphoric acid, for example, with a loading of 5-15 and 5-30 phr). A suitable amount of emulsifier may be, for example, from about 0.1 to about 15 phr, or from about 0.1 to about 5 phr.

[0046] HTC lignin and optional other components are incorporated into the elastomer according to known methods such as described in ASTM D3182-21b. The amount of HTC lignin is 50 phr or more, preferably 60 to 100 phr, and most preferably 90 phr or more.

[0047] The composition according to the invention can be formulated with the aid of a vulcanization reactant, activator, catalyst or accelerator, such as ZnO and / or sulfur and / or an accelerator activator and / or a sulfur donor / accelerator, such as: thiazoles, sulfenamides, guanidines, dithiocarbamates and thiuram sulfides, for example thiocarbamamyls, dithiocarbamoyls, alkoxythiocarbonyls, dialkylthiophosphoryls, diamino-2,4,6-triazinyls, thiuram xanthates and / or alkylphenols. A preferred thiazole is dibenzothiazole disulfide (MBTS), and a preferred thiuram is tetramethylthiuram monosulfide (TMTM). A preferred alkylphenol is poly-tert-amylphenol disulfide. When used, suitable accelerators can be added, for example, in an amount of about 0.1 to about 10 phr, or about 0.1 to about 5 phr.

[0048] The composition according to the invention is useful for manufacturing technical rubber articles such as belts, transmission belts and hoses. It is particularly useful in rubber articles such as hoses which require gas impermeability. Its unique properties are particularly useful in liners.

[0049] The innerliner is a rubber inner layer used in tubeless pneumatic tires, i.e. pneumatic tires without air chambers, to ensure its sealing under the pressure of the air contained in the chamber of the pneumatic tire. The innerliner must ensure that the oxygen in the air charge remains confined in the chamber as much as possible and does not diffuse into parts of the pneumatic tire, thereby causing degradation phenomena. Therefore, the material used for the innerliner must exhibit excellent gas barrier properties. In addition, it must exhibit this property at a minimum thickness, since increasing the thickness leads to a series of disadvantages in terms of weight increase and compromise in terms of rolling resistance.

[0050] Preferably, the composition of the present invention is an innerliner comprising HTC lignin and halogenated butyl rubber.

[0051] Example

[0052] Samples A, B, D and F (comparative) and samples C, E and G (invention) were prepared based on the composition in Table 1. The powder and oil components were added to the polymer, followed by mixing for 7 minutes (ramp down) in a Banbury mixer having a chamber volume of 1,600 ccm, set at 40° C. and 60 rpm (70% fill factor). Subsequently, a curing agent was added, and mixing was continued for 4 minutes. A plate having a thickness of 0.5 mm was formed, and the plate was subjected to curing at 170° C. for 35 minutes. The plate was subjected to the test described below.

[0053] Air permeability was evaluated according to ASTM D1434-82 (09) e1 using a LabThink VAC-V1 gas permeability tester. 2 The nitrogen permeability is measured on the sample test area.

[0054] Tensile properties were measured according to ASTM D412-16 at 23° C. and 100° C. The 100° C. samples were conditioned in an environmental chamber maintained at 100° C. for 30 minutes prior to testing.

[0055] Compression set is measured according to ISO 815-1 after 24 hours at 70°C. Density is measured according to ASTM D297.

[0056] Table 1

[0057]

[0058] The data show that the composition according to the present invention produces lower gas permeability compared to carbon black with comparable surface area. Specifically, at a loading of 60phr, the air permeability is reduced by 8% and 26%, respectively. At a loading of 90phr, the reduction reaches 30%. This is unexpected, as the prior art suggests much lower loadings (<45phr) and requires carbon black as a co-filler, or reports not much reduction. In addition, it is noted that if the surface area is low and the loading is high, the effect on air permeability is particularly beneficial. In addition, it is worth noting that the composition of the present invention shows improved M100% and M300% properties, particularly at high temperatures. Other beneficial properties of the composition of the present invention are reduced compression set. Yet another benefit is the reduced density, which allows for a lower weight product with reduced gas permeability.

Claims

1. A composition comprising an elastomeric polymer and 50 phr (parts per hundred parts of polymer) or more of HTC lignin, wherein the HTC lignin has a particle size D of 5 μm or more as determined by ISO 13320:2020 90 and 40 m as determined by ASTM D 6556-14 2 / g or less STSA surface area.

2. The composition of claim 1, wherein the elastomeric polymer is halogenated butyl rubber.

3. The composition according to any one of the preceding claims, wherein the HTC lignin is present in an amount of 60 to 100 phr, preferably 90 phr or more.

4. A composition according to any one of the preceding claims, wherein the HTC lignin has a relative humidity of less than 30, preferably less than 25, more preferably less than 20, still more preferably less than 15 and most preferably less than 10 m / s as determined by ASTM D6556-14. 2 / g or less STSA surface area.

5. A composition according to any one of the preceding claims, wherein the HTC lignin is present in an amount of 90 phr or more and has a molecular weight of 10 m 2 / g or less surface area.

6. A composition according to any one of the preceding claims, wherein D 90 15 μm or larger.

7. An article comprising a composition according to any one of the preceding claims.

8. The article of claim 7, which is a tire, a tire sealant or an innerliner.

9. Use of the composition according to any one of claims 1 to 6 in a gas barrier.

Citation Information

Patent Citations

  • A tyre comprising hydrothermally carbonized lignin

    EP3243877A1

  • Rubber composition for an inner liner for pneumatic vehicle tyres

    EP3974470A1

  • Tyre sealant layer

    WO2016185351A1

  • Lignin-enhanced butyl rubbers

    WO2020140155A1

  • Rubber compound for an innerliner

    WO2020202125A1